Evaluation of three different osteosynthesis methods for mandibular angle fractures: Vertical load test - Pereira-Filho, Valfrido Antonio [UNESP]; Oliveira, Luis Fernando De Gorla [UNESP]; Reis, José Maurício Dos Santos Nunes [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Neto, Rubens Spin [UNESP]; Monnazzi, Marcelo Silva [UNESP] (Wolters Kluwer, 2016)
The aim of this study was to evaluate the mechanical behavior of different rigid fixation methods in mandible angle fractures. Three different plates were tested: one 4-hole grid miniplate, one 8-hole curved grid miniplate, and one 4-hole straight miniplate. For the loading tests, 30 polyurethane hemimandibles sectioned at the angle area to simulate a simple angle fracture were used: 10 hemimandibles for each group. The mechanical evaluation revealed that the straight plate positioned at the tension zone presented the best results in supporting vertical loading in the predefined displacement moments of 1, 3, and 5 mm. Regarding the grid plates, there was no statistically significant difference between the smaller and the larger plate. According to this sample, the straight plate positioned in the tension zone presented better results than the other 2 different grid plates positioned at the neutral zone.
Keywords: Biomechanical test; Grid plates; Mandible fracture; Rigid fixation